A Pengaruh model inkuiri terbimbing berbsasis STEM terhadap keterampilan proses sains peserta didik pada materi Gelombang cahaya kelas XI IPA SMA - Fika Dina Aprilia Aprilia; Mita Anggaryani (PendIPA Journal of Science Education, 2023)
Process skills and creativity in physics learning are associations of thinking. These two things are the main components of physics and the goals demanded by the 2013 curriculum. One learning model that can be applied to improve science process skills using a guided inquiry model based on Science, Technology, Engineering, and Mathematics (STEM). This study aimed to describe the implementation of the guided inquiry model and STEM-based science process skills, as well as the effect of the STEM-based guided inquiry model on students' science process skills in the material of light waves in class XI IPA. This research method uses descriptive qualitative and quantitative. The results represent that the STEM-based guided inquiry model was very well implemented. Students' science process skills have increased after applying the STEM-based guided inquiry model. The STEM-based guided inquiry model has a significant effect, with the paired t-test results showing that in the experimental class, the count≥ table is 17.42 ≥ 2.06, while the control class is 10.00 ≥ 2.06. The independent t-test results showed a significant difference between the experimental and control classes indicated with count> table, that is, 5.65 > 2.01.